QIBLA ACCURARY OF THE MAHLIGAI AND PAPAN TINGGI TOMB COMPLEXES AT CENTRAL TAPANULI - Rakhmadi, Arwin Juli; Junaidi, Junaidi (Journal of Contemporary Islam and Muslim Societies, 2022)
Abstract: Several gravediggers only use predictions to determine qibla direction during burials without appropriate instruments. Therefore, this study aims to accurately determine the Mahligai and Papan Tinggi tomb complexes’ qibla direction in Barus, Central Tapanuli, using the theodolite. This is descriptive and qualitative research with data collected through interviews, observations, and documentation. The result showed that the qibla direction in the Mahligai tomb complex is deviated by 1°, 11.8o, and 29o to the north, west-south, and south, respectively. Meanwhile, the qibla direction at the Papan Tinggi tomb complex is deviated 13° to the north and is different from the Mahligai tomb complex. Keywords: qibla direction, Mahligai tomb, Papan Tinggi tomb